A Methodology for Developing Transprofessionalism in Engineers in the Conditions of Post-Industrial Society - Zeer, E; Symanyuk, E (KnE Life Sciences, 2018)
The relevance of the problem under consideration is conditioned by the changes in socio-economic conditions and the socio-technological development of the Russian economy, which has significantly altered the world of professions in the post-industrial society: some professions are disappearing, some are transforming, and others are appearing. Along with the traditional concepts of ”profession” and ”specialism”, a new term has been recently established in the field of professional studies: ”transfession”, referring to a kind of labour activity realised based on synthesis and convergence of professional competences belonging to different specialist fields. The main professional characteristic of transfessions is transprofessionalism - the ability to perform a wide range of specialised activities. The identification of socio-humanitarian technologies for the development of this integral capacity of professionals in the system of continuous education determines the relevance of this study. The purpose of the article is to analyse and generalise the grounds and prerequisites for transprofessionalism as an integral quality of the subject of technical professions in a dynamically changing social and professional environment. The main methods in the study of this problem are theoretical and methodological analysis of the research subject and the research problem based on studying and logically generalising scientific research literature, as well as hypothetical-inductive and project methods. The description of the phenomenon of transprofessionalism was made relying on multidimensional, transdisciplinary, network and project approaches. The article presents the scientific definition of transprofessionalism, its meaningful content, as well as criteria of transprofessionalism manifestation in a dynamically changing social and professional environment. The relevance of the phenomenon of transprofessionalism is substantiated understood as requirements to the subject and its integral quality, which implies qualitatively new content and technological training for professionals in technical fields. In particular, it is stated that in the course of post-industrial society development the concept of “profession” loses its original meaning as a field of social division of labour, and transprofessionals capable of performing a wide range of professional activities become competitive and popular on the employment market. The article may be of interest to methodologists, researchers, teachers and those involved in continuing professional education. Keywords: methodology, transprofessionalism, subject of technical professions, logical and semantic model and platform for the development of transprofessionalism, high humanitarian technologies.